Protective antibodies against Clostridium difficile are present in intravenous immunoglobulin and are retained in humans following its administration. (16th March 2017) - Negm, O. H.; MacKenzie, B.; Hamed, M. R.; Ahmad, O. A. J.; Shone, C. C.; Humphreys, D. P.; Ravi Acharya, K.; Loscher, C. E.; Marszalowska, I.; Lynch, M.; Wilcox, M. H.; Monaghan, T. M.
Summary: The prevalence of serum antibodies against Clostridium difficile (CD) toxins A and B in healthy populations have prompted interest in evaluating the therapeutic activity of intravenous immunoglobulin (IVIg) in individuals experiencing severe or recurrent C. difficile infection (CDI). Despite some promising case reports, a definitive clinical role for IVIg in CDI remains unclear. Contradictory results may be attributed to a lack of consensus regarding optimal dose, timing of administration and patient selection as well as variability in specific antibody content between commercial preparations. The purpose of this study was to investigate retrospectively the efficacy of three commercial preparations of IVIg for treating severe or recurrent CDI. In subsequent mechanistic studies using protein microarray and toxin neutralization assays, all IVIg preparations were analysed for specific binding and neutralizing antibodies (NAb) to CD antigens in vitro and the presence of anti‐toxin NAbs in vivo following IVIg infusion. A therapeutic response to IVIg was observed in 41% (10 of 17) of the CDI patients. Significant variability in multi‐isotype specific antibodies to a 7‐plex panel of CD antigens and toxin neutralization efficacies were observed between IVIg preparations and also in patient sera before and after IVIg administration. These results extend our current understanding of population immunity to CD and support the inclusion of surface layer proteins and binary toxin antigens in CD vaccines. Future strategies could enhance IVIg treatment response rates by using protein microarray to preselect donor plasma/serum with the highest levels of anti‐CD antibodies and/or anti‐toxin neutralizing capacities prior to fractionation. Abstract : Protective antibodies against Clostridium difficile are present in intravenous immunoglobulin and are retained in humans following its administration